The governance model of two French national museums of fine arts relocated in the province: Centre Pompidou Metz and Louvre-Lens - Guy Baudelle; Gerhard Krauss (Belgeo)
The article analyses recent cases involving the creation of subsidiaries of two internationally renowned museums: the Centre Pompidou in Metz and the Louvre in Lens. At first glance, these projects seem to be attempts to reproduce the prototypal Bilbao model defining the mobilization of new cultural equipment for an economic recovery purpose. However the case studies, based on numerous interviews of the main protagonists, show that this original decentralization process of two famous institutions in former industrial cities did not mainly respond to economic goals but to cultural ones. From a theoretical point of view, our assumption is that only the creation of a social network dynamics makes their success possible so that we interpret these cultural projects as triggers for setting in motion previously segregated actors.